2011
DOI: 10.4028/www.scientific.net/msf.682.41
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Temperature-Dependent Compressive Deformation Features of Ultrafine-Grained Ti and Cu Produced by ECAP

Abstract: The temperature-dependent deformation and damage behaviors of ultrafine-grained (UFG) Cu and Ti produced by equal channel angular pressing (ECAP) were investigated and compared. It was found that ECAPed materials with different crystalline structures, e.g. the present fcc Cu and hcp Ti, exhibited significantly distinctive high-temperature deformation and damage characteristics. As the testing temperature is below recrystallization, small- and large-scale cracks or voids formed along the shear bands (SBs) on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…2). Although the growth of grains will promote the occurrence of dislocation slip [16], the remaining of lath structures produced during ECAP processing, as well as a lot of dislocations in the cells and the laths (Fig. 11d-f), still leads to the occurrence of shear deformation, but secondary shear bands are not well developed.…”
Section: Influence Of Pre-annealing On Deformationmentioning
confidence: 99%
See 3 more Smart Citations
“…2). Although the growth of grains will promote the occurrence of dislocation slip [16], the remaining of lath structures produced during ECAP processing, as well as a lot of dislocations in the cells and the laths (Fig. 11d-f), still leads to the occurrence of shear deformation, but secondary shear bands are not well developed.…”
Section: Influence Of Pre-annealing On Deformationmentioning
confidence: 99%
“…Similarly, the work by Valiev et al [15] indicated that controlled annealing could bring about a 30% increase in strength of nanostructured SPD titanium simultaneously with enhanced ductility as compared to the case of as-produced state. However, some investigations [10,16,17] revealed that the microstructural stability of UFG materials produced by SPD also depended upon their crystalline structures. For example, Jiang et al [16] compared deformation characteristics and microstructures of UFG CP Cu and Ti at comparative temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations